การออกแบบระบบสารสนเทศสำหรับการวางแผนและควบคุมการผลิตของโรงงานผลิตอะไหล่ยานยนต์ - เมษ โลนิกขะพงศ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
The purpose of this research is to design the information system for production planning an d control in a spare part factory manufacturing. The factory problems has two folds, (1) there is not the good information management for production planning that cause on ineffective planning, (2) Sale estimates the due date, not consider the standard time for each operation so the delivery date of many orders were delay. The research designs and develops the information system for production planning and control by using MysQL for database system and PHP for User Interface. The Material Requirements Planning was used for purchasing planning and production planning in the IS. This IS composed of 8 modules; (1) IS Technology, (2) Quality Assurance, (3) Inventory, (4) Purchase, (5) Management, (6) Production, (7) Marketing, and (8) User Accounts. The result shown that the production planning was more effective; lead time can be reduced form 330 minutes (5.5 hours) to 80 minutes (1.3 hours), and the quantities of delay orders 92 percent.